INFORMATION SYSTEM FOR OCCUPATIONAL NEUROINTOXICATIONS IDENTIFICATION: CAPABILITIES AND PROSPECTS - A. G. Ivanov (Acta Biomedica Scientifica, 2012)
The article represents main results of the approach to development of information system, for supporting of clinical diagnostic process of occupational neurointoxications identification. The key features and capabilities of the system, are reviewed, and the original algorithmic base of its expert-analytical functions is shown. The directions of further development of the system, and. the ways of its prospective scientific use are revealed.